Prognostic factors in cancer patients infected with SARS-CoV-2: a Latin American country results - Erika Ruiz-Garcia; Adriana Peña-Nieves; Jorge Alegria-Baños; Patricia Cornejo-Juarez; Abelardo Meneses-García; Samuel Rivera Rivera; Juan José Sánchez; Raquel Gerson-Cwilich; Daniela Shveid Gerson; Heriberto Medina Franco; Gabriela Alejandra Buerba; Alicia Acosta Espinoza; et al. (SAGE Publishing, 2021)
Purpose: The aim of this study was to evaluate the demographic characteristics, clinical and pathological factors, and the outcome of cancer and COVID-19 patients in Mexico. Patients and methods: A prospective, multicentric study was performed through a digital platform to have a national registry of patients with cancer and positive SARS-CoV-2 test results through reverse transcription quantitative polymerase chain reaction (RT-qPCR). We performed the analysis through a multivariate logistic regression model and Cox proportional hazard model. Results: From May to December 2020, 599 patients were registered with an average age of 56 years with 59.3% female; 27.2% had hypertension. The most frequent diagnoses were breast cancer (30.4%), lymphoma (14.7%), and colorectal cancer (14.0%); 72.1% of patients had active cancer and 23.5% of patients (141/599) were deceased, the majority of which were men (51.7%). This study found that the prognostic factors that reduced the odds of death were gender (OR = 0.42, p  = 0.031) and oxygen saturation (OR = 0.90, p  = 0.0001); meanwhile, poor ECOG (OR = 5.4, p  = 0.0001), active disease (OR = 3.9, p  = 0.041), dyspnea (OR = 2.5, p  = 0.027), and nausea (OR = 4.0, p  = 0.028) increased the odds of death. In the meantime, the factors that reduce survival time were age (HR = 1.36, p  = 0.035), COPD (HR = 8.30, p  = 0.004), having palliative treatment (HR = 10.70, p  = 0.002), and active cancer without treatment (HR = 8.68, p  = 0.008). Conclusion: Mortality in cancer patients with COVID-19 is determined by prognostic factors whose identification is necessary. In our cancer population, we have observed that being female, younger, non-COPD, with non-active cancer, good performance status, and high oxygen levels reduce the probability of death.